(E)-4-{[(3-Propyl-5-sulfanylidene-4,5-dihydro-1H-1,2,4-triazol-4-yl)imino]methyl}-3-(p-tolyl)-1,2,3-oxadiazol-3-ium-5-olate - Fun, Hoong-Kun (International Union of Crystallography, 2011)
The title compound, C(15)H(16)N(6)O(2)S, exists in a trans configuration with respect to the acyclic N=C bond. The 1,2,3-oxadiazol-3-ium ring makes dihedral angles of 10.59 (8) and 73.94 (8)°, respectively, with the 1,2,4-triazole and benzene rings. The molecular structure is stabilized by an intramolecular C—H⋯S hydrogen bond, which generates an S(6) ring motif. In the crystal, molecules are linked into inversion dimers by pairs of intermolecular N—H⋯S hydrogen bonds, generating eight-membered R (2) (2)(8) ring motifs. The dimers are further connected by C—H⋯O hydrogen bonds, forming a sheet parallel to the bc plane. The ethyl group is disordered over two sets of sites with occupancies of 0.744 (7) and 0.256 (7).